Uji Karakteristik Fisik Dan Uji Iritasi Krim Ekstrak Daun Waru Laut (Hibiscus tiliaceus L.) - Kristiani, Monica; Filadelfian, Shallom (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Sea hibiscus leaves (Hibiscus tiliaceus L.) are useful as antioxidants because they contain flavonoids that can ward off free radicals. The flavonoids produced in sea waru leaves are 50%, namely 1.43 mg/mL. Antioxidant compounds can be made into cosmetic preparations, for example, cream, because they have a moisturizing effect on the skin. Physical characterization of the preparation is important to determine the quality of the preparation. Cream preparations need to be tested for irritation to see skin reactions such as erythema and edema, to ensure the safety of a preparation before being used on human skin. This research aims to determine the results of the characterization and skin irritation effects of raw materials or final products from sea waru leaf extract cream preparations. This research is an exploratory experimental method. The research stages include extracting sea waru leaves using the remaceration method with 96% ethanol solvent. The results of sea waru leaf extract were tested qualitatively for flavonoid compounds. The cream is then evaluated for its physical characteristics including organoleptic, homogeneity, pH test, viscosity, spreadability, stickiness, washability, protective power and type of cream. The research results showed that the physical characteristics met the requirements and the cream irritation test showed that it did not irritate in the form of erythema and edema on the skin.